Erosion characterization in urban area in the municipality Itabira, MG (Research, Society and Development, 2017)
The process of soil erosion begins with the removal of native vegetation, which exposes the soil surface to the impact of raindrops, whose kinetic energy causes the destruction of its structure, releasing the different constituents of the texture to be carried by the wind and by the floods. In this sense, the disorderly growth of cities brings serious problems for the urban space, mainly related to subdivisions and waterproofing, which can trigger and / or intensify erosion processes. Thus, this research aimed to characterize, from a geological perspective, three ravines located in the neighborhoods of Colina da Praia (Rav 1), Ribeira de Baixo (Rav 2) and Praia (Rav 3), in the city of Itabira (MG), identifying the factors that favor its development. The analysis of the satellite images allowed to indicate the anthropic interference in these areas, evidenced by the removal of vegetation, opening of lots and streets. As for the geological characterization, it is possible to emphasize the presence of schist rock and granitic-gneiss rock, as well as similar orientations between the direction of ravines 1 and 3 with the fracture planes obtained. Considering the granulometric analysis of soil samples of the three ravines analyzed, it is verified the predominance of soil with medium texture, which commonly has a medium erodibility index. However, the anthropic interference characterized by the removal of the vegetation cover and the opening of road, together with the geological structuring, are factors that contribute, inseparably, to the development of the erosive processes analyzed. The importance of pedological surveys for proper land use planning is emphasized, which will minimize the negative impacts of natural environments.